Herpes Simplex Virus Glycoproteins: Isolation of Mutants Resistant to Immune Cytolysis - Machtiger, N. A. (1980)
Immune cytolysis mediated by antibody and complement is directed against components of the major herpes simplex virus (HSV) glycoprotein complex (molecular weight, 115,000 to 130,000), comprised of gA, gB, and gC, and against glycoprotein gD—all present on the surfaces of infected cells. Tests with a temperature-sensitive (ts) mutant of HSV-1 (tsA1) defective in glycoprotein synthesis at the nonpermissive temperature (39°C) demonstrated that over 90% of mutant-infected cells maintained at 39°C and treated with antibody and complement were not lysed, presumably due to the absence of viral glycoproteins on the surface of infected cells at this temperature. Furthermore, a small number of tsA1-infected cells could be detected among a large excess of wild-type virus-infected cells by virtue of their failure to be lysed at 39°C by antibody and complement. Making use of the involvement of viral glycoproteins in immune cytolysis and the ability of cells infected with glycoprotein-defective mutants to escape cytolysis, we sought mutants defective in the expression of individual viral glycoproteins. For this purpose, antisera directed against the VP123 complex and against the gC and combined gA and gB glycoprotein subcomponents of this complex were first tested for their ability to lyse wild-type virus-infected cells in the presence of complement. Wild-type virus-infected cells were lysed after treatment with each of the three antisera, demonstrating that the gC glycoprotein and the combined gA and gB glycoproteins can act as targets in the immune cytolysis reaction. Next, these antisera were used to select for mutants which were resistant to immune cytolysis. Cells infected with wild-type virus which had been mutagenized with 2-aminopurine and incubated at 39°C were treated with one of the three types of antisera (anti-VP123 complex, anti-gC, or anti-gAgB) and lysed by the addition of complement. Cells which survived immune cytolysis were plated, and virus in the resulting plaques was isolated. Plaque isolates were tested for temperature sensitivity of growth and altered cytopathic effects in cell culture at 34°C (the permissive temperature) and 39°C. A total of 73 mutants was isolated in this manner. Selection with glycoprotein-specific antisera resulted in a 2- to 16-fold enrichment for mutants compared with “mock” -selected mutants using normal rabbit serum. Phenotypically, 24 mutants were temperature sensitive for growth, 27 were partially temperature sensitive, and 22 were not temperature sensitive but exhibited markedly altered cytopathic effects at both permissive and nonpermissive temperatures. Nine mutants of each phenotype (temperature sensitive, partially temperature sensitive, and non-temperature sensitive) were selected at random for confirmatory immune cytolysis tests with the antisera used in their selection. Cells infected with eight of the nine mutants were shown to be significantly more resistant to immune cytolysis at the nonpermissive temperature than were the mock-selected mutants or the wild-type virus from which they were derived.